2014
DOI: 10.1007/s00204-014-1290-y
|View full text |Cite
|
Sign up to set email alerts
|

In vivo toxicity, metabolism and pharmacokinetic properties of FAK inhibitor 14 or Y15 (1, 2, 4, 5-benzenetetramine tetrahydrochloride)

Abstract: Y15 or inhibitor 14 (1,2,4,5-benzenetetramine tetrahydrochloride) is a potent and specific inhibitor of focal adhesion kinase that inhibits its autophosphorylation activity, decreases the viability of cancer cells, and blocks tumor growth. In this preclinical study, we analyzed the pharmacokinetics of Y15 in mice plasma, its metabolic stability in mouse and human liver microsomes and toxicity in mice. The pharmacokinetics study in mice demonstrated that, following intraperitoneal administration at 30 mg/kg dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…To tackle this question, the effects of the FAK inhibitor Y15 or inhibitor 14 on cell death were tested. The inhibitor Y15 is known to specifically inhibit the autophosphorylation of FAK (at Tyr-397) and decrease cancer cell viability and block tumor growth (55)(56)(57). As expected, Y15-treated cells showed a decrease in phosphorylated FAK (Tyr(P)-397) that occurred as early as 15 min post-treatment (Fig.…”
Section: Tablesupporting
confidence: 66%
“…To tackle this question, the effects of the FAK inhibitor Y15 or inhibitor 14 on cell death were tested. The inhibitor Y15 is known to specifically inhibit the autophosphorylation of FAK (at Tyr-397) and decrease cancer cell viability and block tumor growth (55)(56)(57). As expected, Y15-treated cells showed a decrease in phosphorylated FAK (Tyr(P)-397) that occurred as early as 15 min post-treatment (Fig.…”
Section: Tablesupporting
confidence: 66%
“…Fasudil, a small molecule ROCK inhibitor that has been approved for clinical use in Japan and shown to ameliorate experimental lung fibrosis, may be further explored for treatment of liver fibrosis. On the other hand, FAK inhibition has also been shown to prevent experimental lung fibrosis, and toxicity studies in vivo showed that FAK inhibitor 14 does not have significant systemic effects . Given our results showing that FAK is activated by levels of matrix rigidity measured in fibrotic livers and detected in hepatocytes near fibrotic tracts in vivo , it will be of interest in future studies to determine whether FAK inhibition may have a therapeutic role in chronic fibrotic liver disease.…”
Section: Discussionmentioning
confidence: 72%
“…during a 7-day study, has been published recently. There were no chemical, hematological, or histopathological clinical changes in different organs of mice at those two dosages (30).…”
Section: Resultsmentioning
confidence: 83%